A atuação do Ministério Público do Trabalho no combate à corrupção - Balazeiro, Alberto Bastos (2018)
The fight against corruption requires the union of all the institutions of the Brazilian state. The Public Labor Ministry has to be integrated with the list of institutions that have the fight against corruption as one of its goals, since it is a transversal issue that also affects labor relations, especially when it involves public administration. The work of the Public Prosecutor's Office in the fight against corruption must be guided by the search for resolve and the structuring of more perennial solutions. There are legal instruments that can be used by the Public Ministry of Labor in the fight against corruption. It is necessary to resume the debate about the application of the Institutes of the Administrative Improbity Act in the labor jurisdiction and, likewise, to use tools and concepts of the so-called Anti-Corruption Law (12.846 / 2013) in the clauses of proposed terms of conduct and in requests for civil actions filed by Parquet. The Public Prosecutor's Office must work together with other branches of the Brazilian Public Prosecutor's Office in actions to combat corruption, also articulating before the National Congress amendments to the Brazilian Constitution that confer criminal jurisdiction to the Labor Court. It is possible to propose to the parties involved and to the Judiciary that structuring decisions be adopted that will enable a deeper fight against corruption that also affects working relationships. The Public Prosecutor's Office needs to assume its important role in the subject, instituting a specific institutional project to deal with the fight against corruption and contributing to the fact that work relations are based on ethics and probity.